Analisis Prestasi Belajar Dan Motivasi Belajar Siswa SMK Dalam Melanjutkan Pendidikan Ke Perguruan Tinggi - Barkudin Barkudin (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the interest and motivation of vocational school students in continuing their education to higher education. This type of research is quantitative descriptive. The research population was students from Tunas Bangsa Vocational School, while the research sampel was students in class XII, totaling 142 people and 59 people as the sample. The research methode used is quantitative, where the author analyzes the relationship between variables using SPSS version 25 software. The results of the analysis of the classical assumption test with the normality test proved that the data was not normally distributed. The results of the analysis of the relationship between variables prove that learning achievement has an influence on interest in continuing higher education, as well as learning motivation has a positive and significant impact on interest in continuing higher education. Simultaneous test results of learning achievement and learning motivation have a positive and significant effect on ineterst in continuing higher education, the contribution of learning achievement and learning motivation to interest in continuing higher aducation is 67,8% and the remainder is influenced by other variables not researched by the author.